(untitled) (Estudios Sociales, 2019)
The article analyses the beginning and the actions of the Working Group Itaipu Saúde, considering the issues of international cooperation and public policies. The WG is an initiative that provides ways to solve public health problems in the region of the Triple Frontier (Argentina-Brazil- Paraguay). The paper works with interviews, documents and observations of the discussions collected during meetings of the WG Itaipu. As a result, it was possible to verify the history of the group and to understand the functioning of the WG. It was concluded that the WG started as an attempt of international cooperation, which has become a type of actor that enables public health policies in the region of the Triple Frontier.